(untitled) (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The world population is continuously ageing, and a significant amount of world efforts has already been dedicated to increasing the quality of life of the population in the age-group of 65+. A way to achieve this goal is to introduce older generations to the benefits of digital technology. This paper presents the findings of a study on digital technology adoption and the online information needs of senior citizens in the city of Osijek, Croatia. Methodology. The study was conducted on a sample of 188 participants from September to December 2021. The data was collected by the means of a paper survey distributed to respondents in several locations: a local senior care home, the farmers market, and a non-profit organization. Findings. The respondents in our sample prefer smartphones (49.5%) and personal computers or laptops (27.7%) over tablet computers and smartwatches. The internet is used by almost 70% of the respondents, mostly for purposeful searches for information or communication. E-learning, e-shopping, or e-government applications are used rarely. The study detected significant differences in digital technology use concerning gender, age, life satisfaction and living with a partner. Social implications. In order to support and promote the active ageing of senior citizens in Osijek, a more systematic approach at the level of city administration is needed in order to ensure a better understanding and use of digital technology by this vulnerable demographic group. Originality. The paper presents a valuable contribution to further understanding the ICT adoption, skills and online information behaviour of senior citizens in Osijek, Croatia.